Estratégias competitivas para pequenos mercados de Ramilândia -PR - Stahl, Daiani (2024)
The present work aimed to propose strategies for markets A, B and C in Ramilândia - PR, aiming to make them competitive in the face of uncertainties in the consumer goods market. The methodology used was qualitative, exploratory, and descriptive in nature. To collect data, semi-structured interviews were carried out with the owners of markets A, B and C, observations, and a systematic review. To analyze the research data, the content analysis technique was used. The results of this research indicate that, despite the differences between markets A, B and C, they all face common challenges. Although they may vary in their specific characteristics, such as target audience and organizational structure, they share some similar difficulties. Such challenges can be overcome or minimized through specific strategic actions, which tends to contribute to the competitiveness of these small companies. It is suggested, as future research, that a benchmarking analysis be carried out with similar markets in other regions to identify best practices and insights that can be applied to the Ramilândia - PR markets.